SAFETY AND EFFICACY OF ERCP IN OUR INSTITUTION: REVIEW OF 168 CASES - Hasani, Antigona; Tmava, Sabri; Gozalan, Ugur; Vishi, Imri; Hasani, Antigona (International Journal of Innovative Research in Medical Science, 2016)
Background and aims: The objectives of our study were to evaluate the efficacy and safety of this technique performed by two endoscopists with basic training in a center of this nature. Patients and methods: Single center retrospective study of the 168 ERCP performed in our hospital and comparing them with the quality standards proposed in the literature. Results: In this trial, a total of 168 ERCP procedures performed in 153 patients at the endoscopy department of our hospital between January 2010 and December 2010, were retrospectively evaluated. The age, gender, complaints, pre-procedure diagnosis, the radiologic and clinical results, number of procedure repetitions and the final diagnosis were assessed. During the procedure basic patient monitoring was performed. The patients were those admitted to our hospital or referred from other healthcare centers. Conclusions: the results obtained after performing 168 procedures support the ability to practice ERCP in University Clinical Centre of Kosova obtaining levels of efficacy and safety in accordance with published quality standards.